Learning from learning and memory in bumblebees (2009)
The difficulty to simultaneously record neural activity and behavior presents a considerable limitation for studying mechanisms of insect learning and memory. The challenge is finding a model suitable for the use of behavioral paradigms under the restrained conditions necessary for neural recording. In honey-bees, Pavlovian conditioning relying on the proboscis extension reflex (PER) has been used with great success to study different aspects of insect cognition. However, it is desirable to combine the advantages of the PER with a more robust model that allows simultaneous electrical or optical recording of neural activity. Here, we briefly discuss the potential use of bumblebees as models for the study of learning and memory under restrained conditions. We base our arguments on the well-known cognitive abilities of bumblebees, their social organization and phylogenetic proximity to honeybees, our recent success using Pavlovian conditioning to study learning in two bumblebee species, and on the recently demonstrated robustness of bumblebees under conditions suitable for electrophysiological recording.